EXPECTED FUTURE IMAGE FROM INVESTMENT FROM INVESTMENT FOR EDUCATION OF PARENTS’ GENERATION ALPHA STUDENT, A PRIVATE SCHOOL IN BANGKOK - Tongsuk, Pornfa; Ha, Rudiyah; Sukprasert, Tanatpan; Chookamnerd, Woralak (Journal of MCU Nakhondhat, 2024)
The objectives of this study are: 1) To investigate parental expectations, and 2) To present future expectations resulting from educational investments made by parents of Generation Alpha students in Bangkok. Utilizing a qualitative research methodology, data was collected through interviews with 15 informants and semi-structured questionnaires from 191 parents, selected through purposive sampling. The data was analyzed using content analysis, calculating percentage, mean, standard deviation, and cross-impact analysis to study future expectations. The study revealed the following findings: 1) Parental expectations from educational investments for their Generation Alpha children in Bangkok consist of eight aspects: a) Acquisition of fundamental knowledge according to standards, b) A school environment conducive to learning, c) Enhancement of language skills, d) Extracurricular experiences beyond the curriculum, e) A positive school community, f) Good life skills, g) Happiness in attending school, and h) A strong desire to learn. 2) Future expectations from educational investments, as analyzed through cross-impact analysis, indicated six educational management strategies: a) Designing learning activities to help students develop social skills and happiness, b) Developing curricula that emphasize joyful learning and assessing progress through developmental measures rather than achievement, c) Creating curricula that provide knowledge applicable to real life, d) Organizing curricular activities to enhance curiosity and health intelligence, e) Designing learning that fosters ethical and moral development as well as media literacy, and f) Focusing on process skill development through teaching and learning activities.